Forest species for biocultural restoration in eastern Amazon, Brazil - Loch, Vivian do Carmo; Celentano, Danielle; Carvalho Saraiva, Raysa Valeria; T. Alvarado, Swanni; de Freitas Berto , Flávia; Tayllon Serra, Raymony; Castro Barroso, João; Awa Guajá, Tatuxa’a; Xavier Rousseau, Guillaume (Ethnobiology and Conservation, 2023)
Amazon deforestation damages nature, people, and their closer biocultural relationship, eroding fundamental elements for its reproduction. The recognition and use of traditional knowledge to plan and implement restoration efforts are essential to its success. This study identified forest tree species of biocultural value for indigenous communities, quilombolas, and settled farmers in Maranhão state, eastern Brazilian Amazon. Semi-structured interviews, informal conversations, Free Lists, and guided walks were carried out in three different landscapes to identify species with ecological importance and/or use-value according to local communities’ perceptions. Eight categories of species use were defined (food, woody, medicinal, income, cultural, hunting, honey, and energy); and the Smith Salience Index (S) was utilized to identify species with higher importance. A total of 58 native trees (S > 0.1) were listed as biocultural species, five of which were cited for ecological importance only, without a use-value associated. The highest number of species with cultural salience (S > 0.1) was reported in the indigenous group (47), followed by settlers (11) and quilombolas (9). Among the indigenous, we identified a higher number of uses for the same species, and a remarkable spiritual relationship with plants from their cosmological vision. The reproduction of biocultural values in societies needs to receive more attention in the restoration science and praxis. The identification of species of biocultural value can serve as an important ally for the assertive design of conservation and restoration initiatives.